Improving the Effectiveness of the Treatment of Periodontal Disease in Patients with Diabetes Mellitus (Eurasian Research Bulletin, 2023)
Diabetes mellitus (DM) is an endocrine disease with absolute (type I DM) or relative (type II DM) insulin deficiency, causing all types of metabolic disorders [2]. Periodontal diseases are one of the urgent problems of modern dentistry: according to WHO, up to 90% of the adult population worldwide suffers from inflammatory periodontal diseases (IDD). Diabetics suffer from inflammatory periodontal diseases of varying severity in almost 100% of cases. Diabetes affects the rapid progression of periodontal diseases and there is a more severe course of the disease with a significant delay in regenerative and recovery processes [6-9]. Periodontitis in patients with diabetes has a unique morphological structure, characterized by microcirculatory disorders, destruction of the bone tissue of the dentoalveolar system and is directly dependent on the severity of the disease and age; DM is not only a risk factor for the development of periodontal diseases and their further progression, but is also aggravated in the presence of inflammatory processes in the tissues of the periodontal complex [10,13-15]. DM affects all elements of the development of periodontal diseases: blood circulation and sensitivity of nerve endings, immunity and bacterial invasion, regenerative capacity of oral tissues and metabolism of periodontal complex tissues [18]. Damage to microvessels, changes in pain sensitivity thresholds, and conditions favorable for superinfection lead to the development of severe periodontal disease with rapidly increasing tooth mobility and clinically and radiographically detectable significant bone loss. Traditional methods of treatment are ineffective and provide only short-term improvement, without significant remission [2,3,13]. Aggravating factors in patients with diabetes are the high prevalence and intensity of caries, especially proximal and cervical [19]. Wound healing in patients with diabetes mellitus occurs predominantly by secondary intention due to the formation of granulation tissue, which leads to the formation of a microbial reservoir [14-17]. It should be noted that dentists themselves have few guidelines regarding the diagnosis, practice and tactics of treating major dental diseases in patients with diabetes mellitus. The lack of a thoughtful, comprehensive and systematic organization of dental care for patients with diabetes mellitus causes great difficulties for them, makes it impossible to provide timely preventive care in the early stages of the pathological process and leads to the development of inflammation in the tissues of the oral cavity.Underestimation of the relationship between the general condition of the patient and the symptoms of diabetes, ignorance of the specifics of the treatment of diabetes and its complications, the wrong